Controle de umidade da erva mate com o auxílio de sistema embarcado em fase final de secagem - Ribeiro, Lucas Croda (2020)
This article highlights the importance of controlling the moisture content in yerba mate and the lack of verification of this variable in the final stage of the drying process in most industries. The research and construction of a low-cost embedded system for monitoring moisture during the drying of yerba mate (Ilex Paraguariensis) is described, allowing micro and small businesses to qualify the product and ensure the same quality for the consumer. Using cloud-based data storage software and presenting information in a simple way, the project as a whole has become promising for future large-scale commercial development. The metrics established for verifying moisture during production were successful and follow a pattern of data collection over time intervals. The system functioned as expected, with the exception of the sensor used, which does not perform well in its intended function.